Multiple spinal and cranial meningiomas: A case report and review of literature (Journal of Academic Research, 2025)
Though meningiomas are common neoplasms of the nervous system, the occurrence of multiple meningiomas in different neuraxial compartments is rather rare. We report a case of A 28-years old girl presented to neurosurgery outpatient clinic of National Cancer Institute, Misurata - Libya complaining of headache, increased attacks of convulsions (she has been on anti-convulsant since childhood , valproic acid ) and unsteadiness. She walks with assistance and has a history of bowel and bladder dysfunction and right eye visual loss. Her Cranial and spinal magnetic resonance imaging (MRI) revealed multiple homogenously enhancing lesions in the left parieto-temporal region ,craniometrical junction, lumbar and sacral regions..She underwent multiple surgeries including left side frontotemporal craniotomy, suboccipital craniotomy and spinal laminectomy in different sessions and total removal of thd tumors was achieved.Only about 19 cases of multiple cranial and spinal meningiomas have been reported, of which, only five cases have more than one spinal meningioma. The implication of the incidence of such multiple meningiomas in the same patient with relevance to investigations and decision making are discussed along with a brief review of literature of cases with multiple spinal and cranial meningiomas.
Keywords: craniospinal; meningioma; multiple; meningiomas; NF2